On the design of experiments considering the division of the experimental area - Szerszunowicz, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The design of experiments is an important tool to improve production processes that use statistical methods. Designing experiments empowers not only setting properly the parameters of the production process and describing the influence of factors on the results, but also leads to improving the economic results of the analyzed process. The aim of this article is the issue of choosing the appropriate layout of experiments when the experimenter, because of the cost or conditions, has no possibility to implement the completion of the design of experiments. The suggested method takes into account the division of the experimental area and uses measures of spatial autocorrelation to determine the design points to carry out an experiment. The implementation of the mentioned method will be presented for selected factorial designs with particular reference to plans used to estimate the non-linear response surface.
Mathematical Economics, 2012, Nr 8 (15), s. 123-134
Keywords: design of experiments; factorial design; measures of spatial autocorrelation